Combination Of Shibori And Embroidery Techniques In Textile Products - Elvin Setiowati; Theresia Widiastuti (Corak, 2022)
The development of shibori products in the last 5 years has attracted many consumers. This condition is in contrast to the demand for the craft of embroidery. Efforts to combine the shibori and embroidery technique to add aesthetic value and provide a special texture. Besides that, it is expected to produce a different visual appearance from merely giving patterns to fabrics with the shibori technique. The stages of the design method include problem analysis, problem-solving strategies, data collection, and the visual study process. The results of the design are sheets of shibori patterned fabric, namely Arashi shibori and itajime shibori combined with embroidery techniques by raising the idea of dandelion flower motifs on the surface of the fabric to give a new impression on the shibori fabric.